1992
DOI: 10.1111/j.1365-2044.1992.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Colloid solutions in the critically ill

Abstract: SummaryAll patients admitted to an Intensive Care Unit were randomised to receive all volume replacement fluid as either human albumin solution or a synthetic colloid. A total of 475 patients were admitted during the study period. Patients' age, sex, APACHE score and calculated risk of death were assessed on admission. Outcome was assessed as length of Intensive Care stay and mortality. There was no difference between the groups. Subgroups of patients with APACHE score greater than 10, calculated risk of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In an open question, only 2 ICUs specified that they have adapted their strategy according to recently published papers showing the ineffectiveness of volume therapy with albumin with regard to patients' outcome or in elevating a low albumin concentration in the critically ill [8][9][10][11][12][13][14][15]. Astonishingly, on some ICUs albumin is given although the responsible physician is not convinced of its benefit ["forced (not convinced) by the surgeons"].…”
Section: Discussionmentioning
confidence: 99%
“…In an open question, only 2 ICUs specified that they have adapted their strategy according to recently published papers showing the ineffectiveness of volume therapy with albumin with regard to patients' outcome or in elevating a low albumin concentration in the critically ill [8][9][10][11][12][13][14][15]. Astonishingly, on some ICUs albumin is given although the responsible physician is not convinced of its benefit ["forced (not convinced) by the surgeons"].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic colloids, e. g., hydroxyethylstarch solution (HES), are much less costly, but the concerns about the use of HES include possible alterations in coagulation [9,10], allergic reactions, and possible accumulation in the reticuloendothelial system. Volume therapy with albumin is recommended because it is suggested that albumin may bind cations and anions, may serve as a scavenger of free radicals, and may beneficially influence microvascular integrity without exerting any negative effects [11,12]. Unfortunately, in most studies the effects of fluid therapy were assessed over hours rather than over days [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of colloid are available for clinical use—all differ in their molecular weight, colloid osmotic pressure, half-life in the intravascular compartment, and side-effect profile, mainly allergic reactions and adverse effects on coagulation [ 11 , 12 ]. We opted to test one of the modified gelatins, as these are the cheapest, most widely available colloid and have been shown in clinical trials to have a similar efficacy to albumin and other colloids [ 13 – 15 ]. Here we compare the safety and efficacy of Gelofusine (a succinylated modified fluid gelatin 4% intravenous infusion) and albumin in children with severe malaria complicated by metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%